Cardiovascular magnetic resonance in ischemic heart disease. (July 2014) - Bernard, Monique; Jacquier, Alexis; Kober, Frank
ABSTRACT: : Ischemic heart disease is the major cause of death in developed countries. Recently, cardiovascular magnetic resonance (CMR) has appeared as a powerful technique for diagnosis and prognosis of ischemia, as well as for postischemic therapy follow-up. The objective of this chapter is to provide an overview of the role of CMR in assessing ischemic myocardium. It reviews the most recent studies in this field and includes CMR parameters that are already well established in the clinical setting as well as promising or emerging parameters in clinical use.